Volume stability and nano-scale characteristics of concrete composite containing natural zeolite. (1st November 2022) - He, Zhi-hai; Han, Xu-dong; Zhang, Ze-di; Shi, Jin-yan; Han, Chao; Yuan, Qiang; Lu, Jun
Abstract: More environmentally friendly and sustainable cementitious component is essential for improving climate warming and protecting the environment. The effects of zeolite powder (ZP) are investigated in this study on the mechanical properties of concrete and their efficacy in improving the volume stability (dry shrinkage and creep) of the concrete with different specimen sizes. Nanoindentation and scanning electron microscopy are used to characterize the microstructure of concrete. The results show that although ZP reduces the 7-day compressive strength of concrete, the 28-day strength of concrete with 20% ZP is similar to that of the plain concrete. The use of ZP effectively improves the volume deformation of concrete, and concrete with 20% ZP has the lowest dry shrinkage and creep. Meanwhile, an appropriate amount of ZP (20%) can improve the compactness of the microstructure (matrix and interface transition zone) due to its microfiller effect, pozzolanic reactivity and internal curing effect. From the nano-microscale level analysis, ZP can increase the content of high-density calcium silicate hydrate (C–S–H) and reduce the content of low-density C–S–H in the cementitious composition, which is beneficial to the reduction of concrete creep. Graphical abstract: Image 1 Highlights: The long-term volume stability of concrete mixed with zeolite powder was investigated. The nano-scale characteristics of zeolite powder concrete were discussed. The relationship between the nano-scale characteristics of concrete and its dry shrinkage and creep was explained.